Long-term outcomes after in-hospital cardiac arrest: 30-day survival and 1-year follow-up of mortality, anoxic brain damage, nursing home admission and in-home care. (December 2020) - Yonis, H.; Ringgren, K. Bundgaard; Andersen, M. Porsborg; Wissenberg, M.; Gislason, G.; Køber, L.; Torp-Pedersen, C.; Søgaard, P.; Larsen, J. Moesgaard; Folke, F.; Kragholm, K. Hay
Abstract: Aims: Long-term functional outcomes after in-hospital cardiac arrest (IHCA) are scarcely studied. However, survivors are at risk of neurological impairment from anoxic brain damage which could affect quality of life and lead to need of care at home or in a nursing home. Methods: We linked data on ICHAs in Denmark with nationwide registries to report 30-day survival as well as factors associated with survival. Furthermore, among 30-day survivors we reported the one-year cumulative risk of anoxic brain damage or nursing home admission with mortality as the competing risk. Results: In total, 517 patients (27.3%) survived to day 30 out of 1892 eligible patients; 338 (65.9%) were men and median age was 68 (interquartile range 58–76). Lower age, witnessed arrest by health care personnel, monitored arrest and presumed cardiac cause of arrest were associated with 30-day survival. Among 454 30-day survivors without prior anoxic brain damage or nursing home admission, the risk of anoxic brain damage or nursing home admission within the first-year post-arrest was 4.6% ( n = 21; 95% CI 2.7–6.6%) with a competing risk of death of 15.6% ( n = 71; 95% CI 12.3–19.0%), leaving 79.7% ( n = 362) alive without anoxic brain damage or nursing home admission. When adding the risk of need of in-home care among 343 30-day survivors without prior home care needs, 68.8% ( n = 236) were alive without any of the composite events one-year post-arrest. Conclusion: The majority of 30-day survivors of IHCA are alive at one-year follow-up without anoxic brain damage, nursing home admission or need of in-home care.